Internal Water-Induced Acceleration, Chemical Pathways, and Contributing Factors in the Degradation of Poly(lactic-co-glycolic acid) (PLGA) Microparticles and Devices - Mayer, Joseph B.; Patil, Samruddhi M.; Shin, Sung-Ho; Yoo, Jin; Won, You-Yeon (American Chemical Society, 2025)
Poly(lactic acid) (PLA) and poly(lactic-co-glycolic acid) (PLGA) are FDA-approved, biodegradable polymers widely used in medical applications, especially in controlled drug release systems and surgical devices. To be able to predict and control the degradation kinetics of such systems, it is essential to study the effect of various parameters on the degradation rate. In this work, a review is presented concerning the hydrolytic degradation of PLA and PLGA. The effects of solvent dielectric constant, pH, lactate and glycolate content, stereoisomers and crystallinity, degradation temperature, glass transition temperature (T g), and melting temperature (T m), monomer sequence in PLGA copolymers, and polymer molecular weight in PLA/PLGA are reviewed. In vitro/in vivo correlation (IVIVC) limitations are addressed. The main purpose of this paper is to provide a comprehensive review of the results on the hydrolytic degradation of PLA/PLGA available in the literature and to offer clarification on certain aspects that remain less well understood. In particular, we aim to provide insights into the factors underlying the varying and sometimes contrasting findings reported in relatively recent studies. We propose a new explanation for accelerated degradation in the core of PLA/PLGA matrices-internal water-induced acceleration-and discuss how this perspective offers an alternative to existing acid-acceleration models, which appear insufficient to explain some of the more recent data. Additionally, we address topics related to (i) the absence of the backbiting reaction in bulk matrices, (ii) the presence and influence of mass transport of both water and the degradation products, and (iii) the effect of monomer sequence on PLGA copolymer degradation.